Culture "Massorong" in Sociology Religion Perspective - Mirawati; Wahyuddin Bakri; Abd Wahidin (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2022)
In people's lives, of course, there are beliefs such as religion and culture, which can lead to the perspective that many cultures are not in line with religion. This fact is reflected in the Pekkabata people who are Muslim but still uphold the massorong culture. The purpose of this study is to 1) describe the form of the massorong cultural process in the Pekkabata Village community, Duampanua District, Pinrang Regency and 2) to describe the views of the Muslim community in responding to massorong culture. This study uses descriptive qualitative methods and uses observation, interview and documentation data collection techniques The researchers obtained from primary data sources derived from observations at the location and secondary data sources derived from documentation and from several references, with reference to the theory used by researchers so as to be able to explain phenomena at the research location. The results showed, 1) The value of massorong culture in The Pekkabata community is a social fact that is related to the sociology of religion such as the process of preparing for the implementation requires cooperation and mutual cooperation, each of these processes shows the meaning of Sociology of Religion, namely the existence of social actions for the sake of the interests of the community. 2) It has a big impact for the community to do because with this culture, mutual cooperation and mutual help are so strong in society, so that a harmonious and peaceful life can be established with the establishment of good friendship. This massorong culture is actually a much stronger guideline, binding even to the point of being solid (solidarity) towards the formation of individual personalities and social groups. Like this massorong culture, it can be passed down from generation to generation and form a solid person in social life.